Journal of international economic law. (Oxford : Oxford University Press, 1998)
The Journal of International Economic Law is dedicated to encouraging thoughtful and scholarly attention to a very broad range of subjects that concern the relation of law to international economic activity. The journal provides the major English language medium for publication of high-quality manuscripts relevant to the endeavours of scholars, government officials, legal professionals, and others.
Description based on online resource; title from home page (viewed on September 29, 2016).
Keywords: International economic relations -- Periodicals; Law and economics -- Periodicals